METHODOLOGY FOR THE EFFECTIVE USE AND TEACHING OF INFORMATION CULTURE TO STUDENTS IN THE HIGHER EDUCATION SYSTEM - Xolmatova Ziroat Anvarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the political, social, commercial or cultural interests of information transmitters in the conditions of formation, critical reception and creation of Information Culture, identification of information sources in the process of using the universal Internet network for students in the higher education system.